Analysis the Appropriate using Standard Costing Applying in Land Cost Component of Real Estate Development Activities: A Case Study of PT Subur Agung - Yanti, Elfrida (Binus Business Review, 2011)
Standard cost is generally used by manufacturing business, which direct material, labor, and factory overhead are cleared allocated. On real estate business in this case PT Subur Agung use standard cost based on three costs, raw land, land improvement and interest expense categories instead of direct material, direct labor and overhead. Developer use these cost to predict the project cost and estimate the pre-selling price, in accordance with the cost estimation classification matrix, the variance range is in the expected accuracy rate by testing the variance percentage between standard cost and actual cost. The additional similar projects in PT Subur Agung also follow the same scope. All these evidences have proved the appropriate using standard costing in land cost component of real estate development activities but how it applies this article will analyze in this particular project with using descriptive and exploratory method. The analysis started by knowing the conceptual situation of PT Subur Agung and the data was presented in tables and calculation with detail explanation.Â